Silenced Narratives: Assessing the Human Rights Situations of Indigenous Peoples in the Philippines - Simporios , Lloyd Lyndel (Journal of Interdisciplinary Perspectives, 2024)
This article presents an analysis of the human rights situations experienced by many indigenous peoples (IPs) throughout the Philippines. Through an analysis of various sources, it uncovers a range of alarming violations of human rights confronted by IPs, including forced evictions and land grabbing, as well as the degradation of their cultural heritage. It also emphasizes the historical and inherent rights of IPs concerning ancestral territories and self-determination, as protected by national and international laws. A meticulous evaluation of the Philippine government, particularly the National Commission on Indigenous Peoples, exposes substantial inadequacies when it comes to fulfilling their duty to safeguard these rights and combat human rights violations. Drawing on these revelations, this article emphasizes the imperative for the Philippine government to take resolute action in acknowledging and preserving the rights of IPs. Additionally, this calls for the adoption of an approach based on human rights to effectively tackle the challenges confronted by indigenous communities. Above all, this article underlines the utmost significance of ensuring the complete realization of these rights for IPs in the country. It ardently advocates for unwavering monitoring and dedicated advocacy endeavors in this pivotal sphere, aiming to instigate substantial transformations and address the systemic issues that persist.